PENGARUH CORPORATE GOVERNANCE DAN KINERJA PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN BAGI PERUSAHAAN GO PUBLIC - pipit rosita andarsari (RISTANSI: Riset Akuntansi, 2020)
This study aims to determine the effect of the board of commissioners, audit committees, profitability ratios, leverage ratios, and liquidity ratios on the timely delivery of financial statements. In this study the commissioner variable is proxied by the size of the board members, the audit committee is proxied by the size of the audit committee member, profitability ratio is proxied by ROA, leverage ratio is proxied by DER, and liquidity ratio is proxied by CR. The research sample the basic and chemical sectors listed on the Indonesia Stock Exchange in 2016-2017 using a purposive sampling method. Research data sources secondary. Data analysis techniques logistic regression analysis. The results that the board of commissioners, audit committee, profitability ratio (ROA), and leverage ratio (DER) had no significant effect while the liquidity ratio (CR) had a significant effect on the timeliness of financial statement submission. Keyword : board of commissioners, audit committee, profitability ratio (ROA), leverage ratio (DER) , leverage ratio (DER)